Numerical study on fuel physical effects on the split injection processes on a common rail injection system - Han, Dong; Li, Ke; Duan, Yaozong; Lin, He; Huang, Zhen (Energy conversion and management, 2017)
•Fuel physical effects on the split injection strategies are numerically studied.•The injection mass and pressure propagation at the injector inlet are investigated.•Effects of each individual fuel physical property are isolated.•Effects of fuel density and bulk modulus of compressibility are more pronounced.•Injection dwell time is a crucial parameter influencing the main injection event. As biodiesel can be used as an alternative fuel for diesel engines, the changed fuel physical properties are found to have influences on the injection characteristics. In this study, a one-dimensional hydraulic model was established to identify the isolated effect of fuel density, viscosity and bulk modulus of compressibility, on the injection mass and pressure propagation waves of a split injection strategy on a common rail injection system. The numerical simulation results indicated that fuel density and bulk modulus of compressibility have more prominent influences on the fuel injection mass and pressure fluctuation characteristics at the injector inlet during the main injection event, while fuel viscosity effects are modest. In addition, injection dwell time between the pilot and main injection is also a crucial parameter affecting the injection characteristics of the main injection event, because the lengths of the injection dwell time influence the initial pressures at the start of the main injection stage and the mean pressures of the main injection stage. The change in these pressures finally affects the injection mass in the main injection event. Therefore, specific effects of fuel physical properties on the main injection process are subject to the injection dwell time, i.e. the specific split injection strategy.